Applying unmanned aerial vehicle photogrammetry for measuring dimension of structural elements in traditional timber building. (1st March 2020) - Jeong, Gi Young; Nguyen, Tan No; Tran, Dang Khai; Hoang, Thi Bich Huyen
Highlights: Effects of UAV parameters on photogrammetry on a traditional timber building. Measurement of structural elements in a traditional timber building. 3D reconstruction of a traditional timber building using UAV photogrammetry. Abstract: The goal of this study is to evaluate the application of unmanned aerial vehicle (UAV) photogrammetry to reconstruct a 3D model for dimensional measurements of traditional timber buildings. To evaluate the reliability of UAV photogrammetry, the dimensional measurements of a sample timber building from electronic distance measurement and measuring tape methods are compared to the results from UAV photogrammetry. To calibrate UAV photogrammetry parameters such as image shooting rate, camera angle, flight speed, and flight height, different variations of these parameters are applied. The best reconstruction for a timber structure is found at an image shooting rate of 2 s, flight speed of 1 m/s, and a camera angle of 45 degrees. Using these parameters, the structural elements of a traditional timber building are measured. Differences in the dimensional measurements of the columns and beams between the conventional methods and UAV photogrammetry ranges from 0.21% to 0.91%.